Evaluation of the Implementation of Inclusive Education Policy at Piyeung State Elementary School, Aceh Besar District - Nuhari, Insan; Jalaluddin,; Ilhamsyah , Putra; Azwir, (Jurnal Serambi Ilmu, 2025)
The purpose of this study was to evaluate the implementation of inclusive education policies at SD Negeri Piyeung, Aceh Besar Regency. This study uses a qualitative evaluative approach to the research subjects of SD Negeri Piyeung, Aceh Besar Regency. In-depth interviews, document studies, and observations were used to collect data which were then analyzed using the Edwards III implementation model which looked at communication, resources, and disposition. The results of the study showed that the implementation of inclusive education policies at SD Negeri Piyeung, Aceh Besar Regency was considered good, with an achievement of 65%. Communication is an aspect that still needs a lot of improvement, as is disposition which has not been implemented properly. Meanwhile, the aspect that is already the best is resources. The impact of this policy can be seen from the increasing number of students in regular schools from year to year and the reduction in discrimination experienced by students with special needs by peers, teachers, and the community. Keywords ; evaluation, inclusive education, policy implementation